2020
DOI: 10.1177/1753425920933661
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Nrf2 attenuates chronic suppurative otitis media by inhibiting pro-inflammatory cytokine secretion through up-regulating TLR4

Abstract: Compromised TLR-mediated chronic inflammation contributes to bacterial infection-caused chronic suppurative otitis media, but the mechanisms are unclear. The present study examined the expression status of nuclear erythroid 2-related factor 2 (Nrf2) and TLRs in human middle-ear mucosae tissues collected from patients with chronic suppurative otitis media, chronic otitis media and non-otitis media, and found that Nrf2 was high-expressed, whereas TLR4, instead of other TLRs, was low expressed in chronic suppurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…A comparison of the middle ear mucosa of non-otitis media, COM, and CSOM groups showed that mRNA and protein levels of TLR4 were not different between non-otitis media and COM groups, but were significantly decreased in the CSOM group. These authors thus concluded that reduced TLR4 levels in the middle ear mucosa cause a persistent inflammatory response and weaken susceptibility to CSOM [30,40].…”
Section: Tlr4mentioning
confidence: 97%
“…A comparison of the middle ear mucosa of non-otitis media, COM, and CSOM groups showed that mRNA and protein levels of TLR4 were not different between non-otitis media and COM groups, but were significantly decreased in the CSOM group. These authors thus concluded that reduced TLR4 levels in the middle ear mucosa cause a persistent inflammatory response and weaken susceptibility to CSOM [30,40].…”
Section: Tlr4mentioning
confidence: 97%
“…The Tlr4 gene expression levels were not altered in children with a history of OM compared to control in middle ear tissue samples [15]. Also, the Tlr4 gene expression is downregulated in middle ear tissue samples of CSOM patients in comparison to controls [16]. Together these report suggest that Tlr4 gene expression were downregulated in OM.…”
Section: Discussionmentioning
confidence: 64%
“…In our present study we aim to compare the expression of the TLR4 gene in the blood samples of CSOM patients and healthy controls. A case-control study was carried out by involving 16 participants in each group. The levels of the TLR4 gene expression were measured by using the qRT-PCR method.…”
mentioning
confidence: 99%
“…Therefore, the present study aimed to investigate the NEAT1/miR-301b-3p/TLR4 regulatory network, in the hope of revealing a new theoretical basis for the application of NEAT1 in the treatment of AOM. In the present study, LPS was used to establish the cell model of AOM and investigate the potential mechanism (26,32). According to previous reports, NEAT1 is induced in multiple immune system diseases, such as pneumonia (15), hepatitis (17) and osteoarthritis (33).…”
Section: Discussionmentioning
confidence: 94%